Psychological Well-being among Breast Cancer Patients in Surabaya: An Overview - Hanik Endang Nihayati; RR Dian Tristiana; Widya Fathul Jannah (Poltekkes Kemenkes Palu, 2025)
Patients with chronic diseases like breast cancer experience psychological, biological, social, and spiritual changes or imbalances. Positive psychological well-being does not emerge automatically in breast cancer patients. Many factors influence psychological well-being in these individuals, and their psychological responses and transitions are subjective and rooted in personal experience. This study aimed to identify the psychological well-being of breast cancer patients in Surabaya. The design of this study is qualitative with a phenomenological approach. The study included eight participants who met the research inclusion criteria. Data were collected using an in-depth interview technique. Interpretative Phenomenological Analysis was carried out on the data analysis. The results of this study obtained seven themes, namely loss response, psychological response, relationship with others, decision making, utilization of health services, hope, and self-adjustment. A person diagnosed with breast cancer requires a transition process to achieve comfort with a new situation. This transition process begins with a type of transition in the form of a diagnosis of breast cancer, and transition conditions that may facilitate or inhibit the transition process. These breast cancer patient response patterns are the way patients self-manage in making changes and outcome indicators in the form of positive psychological well-being. Nurses play a crucial role in promoting patients' psychological well-being by regularly performing mental health assessments, attentively listening to emotional concerns, recognizing spiritual needs,